Investigation of container traffic through Singapore - Tan, Wee Kee. (2008)
Examines the historical trends in the container traffic through Singapore and identifies the existing and potential port competitors that Singapore is facing. A comparison of Singapore with two other international seaports - Rotterdam and Long Beach, was attempted and possible factors that would affect the future container traffic through Singapore were identified and analysed.